Correlation between Immature Platetet Fraction Value and SOFA Score in Sepsis Patient - Hesty Rhauda Ashan; Husni Husni; Eugeny Alia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Sepsis is a medical emergency that describes systemic inflammation reaction to infectious process that can lead to organ dysfunction and death. Sequential Organ Failure Assesment (SOFA) score is used to assess severity of organ dysfunction in septic patients. Immature platelet fraction (IPF) value can be used to evaluate thrombopoiesis. Research shows IPF can provide information regarding inflammatory activity and disease prognosis. A high IPF value in septic patient indicates the formation and recruitment of immature platelets that are triggered by infection. The aim of this study was to determine correlation between IPF value and SOFA score in sepsis patients. This was an analytical study with a cross-sectional design in 28 patients with sepsis who met the inclusion and exclusion criteria and conducted IPF tests at Central Laboratory of Dr M. Djamil Padang Hospital. The study was conducted from February 2020 to March 2021. Value of IPF was performed using automated hematology analyzer with flow cytometry method and SOFA scores are assessed by clinicians and obtained from medical records. Data were analyzed by Pearson correlation test, significant if p <0.05. Median value of IPF in patients with sepsis was 4.8 (1.4-15.7) %. Median of SOFA score in patients with sepsis was 5,5 (2-12). Correlation test showed a strong positive correlation between IPF values and SOFA score with r= 0.684 and p <0.05. There was a strong positive correlation between IPF values and SOFA score in sepsis.